Integrated Emergy and Economic Performance Assessments of Maize Production in Semiarid Tropics: Comparing Tillage Systems - Barros, Inacio De; Pacheco, Edson Patto; Carvalho, Hélio Wilson Lemos De (Journal of Environmental Accounting and Management, 2026)
Owing to a combination of factors like improved genotypes, closeness to consuming markets, good infrastructure to production outlets and a rainy period that occurs during the off-season, maize production in the Eastern part of the semiarid tropics (SAT) in Brazil is undergoing a shift towards a farming systems with intensive use of chemical inputs, tillage and high yielding genetically-modified (GMO) hybrids. However, the region is highly prone to desertification, and the intensive tillage accelerates the soil degradation process. Although conservation tillage has been reported to improve soil protection and quality and, consequently, sustainability of cereal production in many environments, farmers are still reluctant to adopt it, fearing yield declines as documented in early studies in SAT. Recent findings however, have shown that no-till can be instrumental for improving soil fertility and crop yields also in semiarid environments. The goals of this study are to assess the environmental and economic performances of conservation tillage in SAT and to compare the environmental performance of maize production in SAT and in more favorable environments for agricultural production in South America. Emergy accounting was used for assessing the environmental performance, and classical economic indicators for assessing the economic performances. Indicators for both environmental and economic aspects showed that no-till improves environmental performance, while it reduces costs and increases profits when compared to reduced and conventional tillage systems for maize production in SAT. Although some emergy indicators are slightly poorer in SAT than in the Atlantic Rainforest, the transformity of maize grains allow us to infer that maize production in SAT makes use of environmental resources more efficiently than in the South of Brazil or in the Argentinean Pampas. Further analysis shows that the higher prices obtained for maize grains in the region seem to pay off for the higher climate risks of Brazilian SAT.